On the Dynamics of Early Multilingualism - Hofer, Barbara (De Gruyter, Inc., 2015)
The series Trends in Applied Linguistics meets the challenges of the rapidly growing field of applied linguistics. In a very broad sense, applied linguistics is understoodby focusing on the application of theoretical linguistics to current problems arising in different contexts of human society. Given the interdisciplinary character of applied linguistics, the series includes cognitive, psycholinguistic, sociolinguistic and educational perspectives. The following topicsare included in the series: Second language acquisition and the acquisition of additional languages Bilingual and multilingual education Language planning and language policy Literacy skills Second/foreign language pedagogy Translation and interpretation Language for specific purposes Discourse analysis Language testing and assessment Child language Language and gender Pragmatics and rhetorics Corpus analysis Critical pedagogies Research methodology in applied linguistics Language and technology. Intro – Table of contents – Acknowledgments – List of figures – Preface – Structure of the book – I. Theoretical background – Theoretical underpinnings in early multilingual instruction – 1. An Introduction to multilingualism – 1.1 On the benefits of an early start – 1.2 Cognitive consequences of being bi/multilingual – 1.3 Recent trends in multilingualism research – 1.4 The dynamics and complexities of multilingual learning and development – 1.5 Third language learning and the role of meta- and crosslinguistic awareness – 1.6 Third language learning and the effects of prior linguistic knowledge – 2. The representation of language in the mind – 2.1 Models of language representation: How are words and concepts represented and interconnected in the mind of bilingual and multilingual speakers? – 2.2 The Word-Association and Concept Mediation Model – 2.3 The Revised Hierarchical Model – 2.4 The Distributed Feature Model – 2.5 The Integrated Model: A model for bilingual language representation and processing – 2.6 Lexical Access in bilingual and multilingual speakers: The language specific and language non-specific perspective – 2.7 A dynamic view of the multilingual lexicon – 3. Language processing – 3.1 Is multilingual processing any different from monolingual or bilingual processing? – 3.2 Language production – 3.2.1 Levelt: A Monolingual Speech Model – 3.2.2 Dell: Spreading Activation Model – 3.3 Multilingual language production – 3.3.1 Poulisse and Bongaerts' Production Model – 3.3.2 Myers-Scotton: A Matrix Language Frame – 3.3.3 Grosjean: The Language Mode Hypothesis – 3.3.4 Green: The Activation/Inhibition model – 3.3.5 Clyne: The Plurilingual Model – 3.3.6 De Bot: The Bilingual/Multilingual Production Model – 3.4 Language comprehension.
Description based on publisher supplied metadata and other sources
Keywords: Bilingualism in children; Child rearing; Child development; Language acquisition; Psycholinguistics; Child development; Psychological aspects; Child rearing; Psychological aspects; Language acquisition; Psychological aspects; Electronic books